2019
DOI: 10.1002/ijgo.12834
|View full text |Cite
|
Sign up to set email alerts
|

Integrating gender perspectives in gynecology and obstetrics: Engaging medical colleges in Maharashtra, India

Abstract: Failure to acknowledge the impact of sex and gender differences affects the quality of health care provision, and is an impediment to reducing health inequities. Systematic efforts were initiated in Maharashtra, India for reducing these disparities by developing gender‐integrated curricula in undergraduate (UG) medical education between 2015 and 2018. A review of UG obstetrics and gynecology curricula indicated a lack of gender lens and focus on the reproductive rights of women. Based on these gaps, a gender‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…The study was carried out at three tertiary medical teaching hospitals: Aurangabad Government Medical College, Aurangabad and Miraj Government Medical College and Sangli District Hospital. These facilities were identified based on their participation in a prior collaborative project with CEHAT on integrating gender within medical education [ 34 ], implemented in these and five other hospitals in the state of Maharashtra. The selected hospitals were attached to the medical colleges that had performed best in terms of integrating modules on gender in pre- service curriculum.…”
Section: Methodsmentioning
confidence: 99%
“…The study was carried out at three tertiary medical teaching hospitals: Aurangabad Government Medical College, Aurangabad and Miraj Government Medical College and Sangli District Hospital. These facilities were identified based on their participation in a prior collaborative project with CEHAT on integrating gender within medical education [ 34 ], implemented in these and five other hospitals in the state of Maharashtra. The selected hospitals were attached to the medical colleges that had performed best in terms of integrating modules on gender in pre- service curriculum.…”
Section: Methodsmentioning
confidence: 99%
“…Most articles assessed medical schools in the United States of America (USA) 2–33 . Additional studies reported sexual and reproductive health education from around the world including Angola, 34 Australia, 35–37 Canada, 38–40 China, 41 the Democratic Republic of Congo, 42 India, 43–45 Iran, 46 Nepal, 47 the Netherlands, 48 Pakistan, 49,50 Turkey, 51 and the United Kingdom 52–54 . Our review largely revealed studies at single medical schools.…”
Section: Resultsmentioning
confidence: 99%
“…16,17,21 Thirty-one studies reported student responses about their knowledge on, perceptions of, or experiences with, sexual and reproductive health teaching . [2][3][4][5]8,9,[13][14][15]18,19,24,[32][33][34][35][36][38][39][40][41]43,44,[46][47][48][49][51][52][53]55,56 Five studies provided insights from medical educators about their experiences with contraception and abortion education. 7,23,48,49,53 Two qualitative studies explored student perspectives on sexual and reproductive health education.…”
Section: Training Level Of Students Assessedmentioning
confidence: 99%
See 1 more Smart Citation
“…Prejudice and limited awareness of SRHR on the part of healthcare workers exacerbate discriminatory care. This should be counteracted by including SRHR for women in general, and for refugees specifically, as a topic in undergraduate and postgraduate curricula and in the education of healthcare providers . Governments must commit to providing non‐discriminatory care for refugees in their countries in alignment with SDGs 3 (ensure healthy lives and well‐being), 5 (achieve gender equality and empower women) and 10 (reduce inequality), and providers must put this into practice.…”
Section: Resource Barriers To Srh Care For Refugees In Low‐income Coumentioning
confidence: 99%